Behavior of a heavy cylinder in a horizontal cylindrical liquid-filled cavity at modulated rotation. (25th August 2016) - Kozlov, Nikolai V; Vlasova, Olga A
Abstract: The behavior of a heavy cylindrical solid in a horizontal cylindrical cavity is experimentally investigated. The cavity is filled with a viscous liquid and rotates. Two rotation regimes are considered. The first one is steady rotation. A number of body motion regimes are found depending on the cavity rotation speed. The second regime is a modulated rotation, in which the rotation speed is varying periodically. It can be presented as a sum of steady rotation and librations. On the whole, three different cases of the body repulsion from the cavity wall are observed. In the first case, the repulsion occurs when the body slides over a rotating cavity wall. In the second case, the body being in the centrifuged state—when it rotates with the fluid—detaches from the cavity wall under the action of gravity. In the third case, at librations, the wall performs oscillations and the body is repulsed from the wall due to the nonlinear viscous interaction with the fluid.